1994
DOI: 10.1111/j.1471-0528.1994.tb13037.x
|View full text |Cite
|
Sign up to set email alerts
|

Taking account of vaginal bleeding in screening for Down's syndrome

Abstract: Objective To derive a method for revising the risk of Down's syndrome in maternal serum marker screening when there is vaginal bleeding. The effect on screening performance of routinely allowing for the presence or absence of bleeding in all women is also assessed. Design Overview of published studies on the rate of reported vaginal bleeding in pregnancies with Down's syndrome, on the rate according to maternal age and on the association of bleeding with alpha‐fetoprotein (AFP) level. The publicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

1995
1995
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 11 publications
0
9
0
1
Order By: Relevance
“…However, comparison of the subgroups of patients with early vaginal bleeding to patients without bleeding showed no significant difference in δ-NT, the MoM's of free β-hCG and PAPP-A. This is in contrast to the effect of early vaginal bleeding on the maternal serum concentrations of αfetoprotein in the first and second trimester of pregnancy (Haddow et al, 1986;Bernstein et al, 1992;Williams et al, 1992;Cuckle et al, 1994;Berry et al, 1995). Our results are in line with those reported by De Biasio et al (2003), who found higher maternal serum levels of free β-hCG in the first trimester after early vaginal bleeding.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, comparison of the subgroups of patients with early vaginal bleeding to patients without bleeding showed no significant difference in δ-NT, the MoM's of free β-hCG and PAPP-A. This is in contrast to the effect of early vaginal bleeding on the maternal serum concentrations of αfetoprotein in the first and second trimester of pregnancy (Haddow et al, 1986;Bernstein et al, 1992;Williams et al, 1992;Cuckle et al, 1994;Berry et al, 1995). Our results are in line with those reported by De Biasio et al (2003), who found higher maternal serum levels of free β-hCG in the first trimester after early vaginal bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…Some kind of vascular disruption at the maternal-fetal interface may be the cause for bleeding to occur. Such an event is likely to affect the maternal serum concentration of proteins produced by the placenta and the fetus, including those used for Down syndrome screening (Cuckle et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 The incidence of vaginal bleeding in pregnancies with Down's syndrome was about 1.7 times more than the unaffected pregnancies. 18 But most of the studies concluded that there was no excess of congenital anomalies of the foetus after vaginal bleeding in first trimester.…”
Section: Discussionmentioning
confidence: 99%
“…Vajinal kanamanın etiyolojisi tam olarak aydınla-tılmamıştır fakat en önemli nedenlerinden biri maternal-fetal yüzdeki desidual damarların ayrılma-sıdır (6,7). Daha önce yapılan çalışmalarda maternal serum Alfa -fetoprotein (AFP) düzeylerinin vajinal kanamadan etkilenebileceği gösterilmiştir (8)(9)(10) . Ayrıca vajinal kanama öyküsü olan hastalarda bazı çalışma-larda serum serbest β-hCG seviyelerinde ve PAPP-A seviyelerinde yükseklik saptanmış olup (11,12) , serum seviyelerinin etkilenmediğini de gösteren çalışmalar mevcuttur (13) .…”
Section: Introductionunclassified